Acute Q fever infection in Thuringia, Germany, after burial of roe deer fawn cadavers (Capreolus capreolus): a case report. (November 2015) - Schleenvoigt, B.T.; Sprague, L.D.; Mertens, K.; Moog, U.; Schmoock, G.; Wolf, G.; Neumann, M.; Pletz, M.W.; Neubauer, H.
Abstract: We report on a case of a 48-year-old man who presented with acute Q fever infection after burying two fawn cadavers ( Capreolus capreolus ). Recent outbreaks of Q fever in Europe have been traced back to intensive goat breeding units, sheep flocks in the proximity of highly populated urban areas or to farmed deer. To our knowledge, this is the first case report describing Q fever infection in a human linked to roe deer as a source of infection.